Entrepreneurship Capital and Economic Performance - David B. Audretsch; Max Keilbach (Max Planck Institute for Research into Economic Systems, 2004)
The neoclassical model of the production, as applied by Robert Solow to built the neoclassical model of growth, linked labor and capital to output. More recently, Romer and others have expanded the model to include measures of knowledge capital. In this paper we introduce a new factor, entrepreneurship capital and why it should influence economic output. A production function model including several different measures of entrepreneurship capital is then estimated for german regions. The results indicate that entrepreneurship capital is a significant and important factor shaping output and productivity. These results suggest a new direction for policy that focuses on instruments to enhance entrepreneurship capital.
Keywords: O47; O32; M13; 330; Produktionsfunktion; Produktionsfaktor; Unternehmer; Unternehmensgründung; Schätzung; Deutschland